Interiorismo de la “Boutique Mandee” de la ciudad de Loja, aplicando el estilo pop-art - Ayala Cumbicos, Pablo Anibal (2015)
Inside the boutique, interior design with pop-art style plays an important role, since this trend born in the decade of the 60's collects images of daily life of human beings and transforms them into decorative objects as the image of the American Andy Warhol transformed the photograph of Marilyn Monroe in an art that continues to this day, as decoration. The boutique is a small clothing store and allows the public who enters can buy clothing. Within this space it is good to consider some aspects such as the facade, showcase, shelves or counters; because in this way you can display the goods and potential customers can see clothes. Lighting is important because we can take advantage of natural light filtering in from the street into the boutique through the window and we also have the artificial light used to illuminate certain areas of the store. Among the boutiques there are some varieties such as classical, modern, romantic, etc. They also play an important role materials used for interior decoration such as: the floor, walls, furniture, etc. The boutique also has areas that are of important nature such as shelves and windows that used to display the goods directly to the public, being placed behind glass. Testers play an important role in the boutique, as these provide the function of providing enough for customers can be tested or measured merchandise that is for sale space. Within the international benchmark, it has been decided that the clothing brand Louis Vuitton, is the most important worldwide representative for showing the inside of her boutiques and clothing designs, design form a set of dream. But all this is also due to the architect and designers, who increasingly are creating new concepts and ideas on what to do with interior design.